Echoes of Emerson in Walt Whitman’s “Song of Myself - Hammah, A. E. (University of Ghana, 2014)
This study explores fundamental relationships existing in the works of two great American Scholars of the 19th century: Walt Whitman and Ralph Waldo Emerson. It argues that, “Song of Myself”, the poetry collection in Whitman’s major literary work Leaves of Grass, echoes or re-emphasizes some of Emerson’s significant ideological and philosophical beliefs. Ralph Waldo Emerson, recognized as the founder of America’s transcendentalist movement, was a key figure in America’s intellectual and literary revolution in the 19th century. Ralph Waldo Emerson’s publication of “Nature” in 1836 began a process of creating a new condition of American thinking, severed from European cultural and intellectual influences.1 In “The American Scholar” and “Self-Reliance”, Emerson called for an original American literature that truly depicted the American taste and condition. His philosophy of “trusting in one’s self”, breaking away from theological and institutional dogmas and believing in the “divine” human personality, influenced other writers like Emily Dickinson, Walt Whitman and Henry David Thoreau just to mention a few. Like Emerson’s first work “Nature” (1836), “Self-Reliance” (1841) was recognized for its peculiar character as a work of social commentary, espousing ideals of ‘how men ought to live’ while deemphasizing the asphyxiating pressures of external authority. The study illustrates the inter-textual ties and influences between Whitman’s long poem “Song of Myself” and aspects of Ralph Waldo Emerson’s major literary works. The study investigates this relationship by examining the thematic and philosophical concerns expressed in Whitman’s poetry and juxtaposes it with its literary predecessor/precursor rooted in a selection of Emerson’s major transcendentalist literary works. Employing T.S Eliot’s theory of influence in “Tradition and the Individual Talent” (1919) as a framework to interpret the echoes, the study challenges traditional notions of influence that privilege the precursor influence as a “standard” to evaluate the later artist’s work and concludes that although Emerson is echoed in Whitman’s text, the relationship of influence between these two writers (per a critical literary interpretation of texts) is not one in which the precursor is seen in the simplistic light of “flowing into”, or sending forth “power or virtue” to the later artist. Rather, the relationship of influence is a sort of symbiosis in which the precursor and the later texts mutually transform and reinforce each other.
Thesis(MPhil) - University of Ghana 2014